2017
DOI: 10.1002/adma.201601128
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporally Controllable Peptide‐Based Nanoassembly in Single Living Cells for a Biological Self‐Portrait

Abstract: Simultaneous precise localization and activity evaluation of a biomolecule in a single living cell is through an enzyme-specific signal-amplification process, which involves the localized, site-specific self-assembly, and activation of a presignaling molecule. The inactive presignaling tetraphenylethylene (TPE)-peptide derivative, TPE-YpYY, is nondetectable and highly biocompatible and these small molecules rapidly diffuse into living cells. Upon safely arriving at an active site, and accessing the catalytic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 42 publications
0
17
1
Order By: Relevance
“…These observations suggested that the tandem self‐assembly of 1 in the extra‐ and intracellular environments of liver cancer cells was due to the high concentrations of both ALP and GSH in liver cancer cells. Although intracellular self‐assembly has recently been demonstrated to be a powerful strategy for the spatiotemporal profiling of enzyme activity, those self‐assembled fluorescent probes did not show obvious fiber structures within the cells, while our results directly and clearly show the formation of intracellular fibers in liver cancer cells. It is important to note that the distribution of nanofibers was different between the QGY7703 and HepG2 cells.…”
Section: Figurecontrasting
confidence: 66%
“…These observations suggested that the tandem self‐assembly of 1 in the extra‐ and intracellular environments of liver cancer cells was due to the high concentrations of both ALP and GSH in liver cancer cells. Although intracellular self‐assembly has recently been demonstrated to be a powerful strategy for the spatiotemporal profiling of enzyme activity, those self‐assembled fluorescent probes did not show obvious fiber structures within the cells, while our results directly and clearly show the formation of intracellular fibers in liver cancer cells. It is important to note that the distribution of nanofibers was different between the QGY7703 and HepG2 cells.…”
Section: Figurecontrasting
confidence: 66%
“…As the cellular uptake of E/Z-TPAN-OM and E/Z-TPAN-OH was limited, E/Z-TPAN-POH modified with phosphate group were further designed to improve their water solubilities and endow them with enzymatic responsiveness, as the phosphate group is the substrate of alkaline phosphatase (ALP) that plays a significant role in cell signaling pathway and has become an important biomarker in cancer diagnosis. [50][51][52][53] The obtained E/Z-TPAN-OM isomers retained the same stereo-structure as their individual precursor and displayed different fluorescence quantum yields. As the E/Z-TPAN-POH and their hydrolysis product, E/Z-TPAN-OH (Figure 7a), eluted out with different time scales, the ALP-catalyzed hydrolysis of E/Z-TPAN-POH could therefore be quantitatively monitored by HPLC.…”
Section: Divergency In Enzymatic Responsivenessmentioning
confidence: 91%
“…modified with phosphate group were further designed to improve their water solubilities and endow them with enzymatic responsiveness, as the phosphate group is the substrate of alkaline phosphatase (ALP) that plays a significant role in cell signaling pathway and has become an important biomarker in cancer diagnosis. [50][51][52][53] The obtained E/Z-TPAN-OM isomers retained the same stereo-structure as their individual precursor and displayed different fluorescence quantum yields. As the E/Z-TPAN-POH and their hydrolysis product, E/Z-TPAN-OH (Figure 7a), eluted out with different time scales, the ALP-catalyzed hydrolysis of E/Z-TPAN-POH could therefore be quantitatively monitored by HPLC.…”
Section: As the Cellular Uptake Of E/z-tpan-om And E/z-tpan-oh Was Limited E/z-tpan-pohmentioning
confidence: 91%